The Role Of The Tax Court In Resolving Tax Disputes: An Analysis Of The Effectiveness And Transparency Of The Legal Process - Ayudia Rizqa Fadhlia (SEAN Institute, 2025)
The Tax Court plays a strategic role in resolving tax disputes to establish a transparent and effective taxation system. Its existence is crucial not only for providing legal certainty for taxpayers but also for enhancing the credibility of the overall tax system in Indonesia. The Tax Court serves as the judiciary body handling disputes between taxpayers and the Directorate General of Taxes. This study aims to deeply examine the court's function in tax dispute resolution and the factors affecting the effectiveness and transparency of the legal processes. This research employs a juridical-normative approach supported by analysis of court decisions and relevant case studies. The study identifies several challenges in resolving tax disputes, including prolonged dispute resolution periods, limited access to court decisions, and taxpayers' insufficient understanding of legal procedures. While progress has been made in the implementation of the Tax Court, the findings highlight the need for policy reinforcement and enhanced accessibility to improve the quality of services and transparency in the Tax Court system. Based on these findings, the study provides recommendations to improve the effectiveness and transparency of the Tax Court. The research is expected to serve as a foundation for enhancing Indonesia's tax legal system, aiming to create a more just, efficient, and accessible taxation framework for all citizens.